The Final Dismissal of the Lawsuit and its Legal Effects in Jordanian Law - Musaed Bin Mahawsh Alghalwain Alfahiqi (Journal of Legal Sciences, 2024)
The research aims to show what the final dropping of the lawsuit is, and the legal consequences of the dropping. The researcher used the descriptive and analytical approach, and the research showed that the Jordanian legislator has introduced by virtue of the recent amendment to the clause contained in the second paragraph of Article No. 125 of the amended law of the Jordanian Civil Procedure Code No. 6 of the year an amended law of the Civil Procedure Code No. 6 of the year published on page 1866 of the official gazette No. 5922 dated 2024/4/16, which states that the lawsuit is considered invalid if dropped for more than two years on two years. Which is what he meant by the final dismissal of the lawsuit, which is to get rid of the antagonism and treat it as if it were not.